A Participatory Approach to Building Human Capital : Morocco's National Human Development Initiative - Global Delivery Initiative (Global Delivery Initiative, Washington, DC, 2020)
From 2000 to 2020, Morocco made significant strides in improving both its economic and its social status. Compared to the growth rates it maintained on average during the 1980s and 1990s, it increased its GDP growth rate and diversified its economy by focusing on sectors that had growth potential, such as the aeronautical, automobile, and solar energy industries. Encouraged by the positive results and improved indicators, Morocco strove to close its economic gap quickly and join the ranks of upper-middle-income countries. From a social standpoint, the country’s performance was also sound. It significantly reduced overall poverty and nearly eradicated extreme poverty. Over that 20-year period, Morocco also made progress in developing its human capital. A prominent national program driving the development of the country’s human capital was the National Human Development Initiative (NHDI). Launched in 2005 by King Mohammed VI, he described it as “a royal project that places the human element at the center of national policies.” The main goal of the NHDI was to address critical gaps in Morocco’s development trajectory, such as high poverty in rural areas, social exclusion in urban areas, and the lack of opportunities and resources available to vulnerable populations (Benkassmi and Abdelkhalek 2020; World Bank 2017a). It was designed to improve socioeconomic conditions in targeted poor areas through participatory local governance mechanisms. The government implemented the initiative at the level of rural and urban local governments (known in Morocco as communes) and in urban neighborhoods (Bergh 2012). The program was implemented in multiple phases, adapting to changing circumstances as it facilitated projects that advanced human capital development.